Biomorphous SiC ceramics prepared from cork oak as precursor. (April 2016) - Yukhymchuk, V.O.; Kiselov, V.S.; Valakh, M.Ya.; Tryus, M.P.; Skoryk, M.A.; Rozhin, A.G.; Kulinich, S.A.; Belyaev, A.E.
Abstract: Porous ceramic materials of SiC were synthesized from carbon matrices obtained via pyrolysis of natural cork as precursor. We propose a method for the fabrication of complex-shaped porous ceramic hardware consisting of separate parts prepared from natural cork. It is demonstrated that the thickness of the carbon-matrix walls can be increased through their impregnation with Bakelite phenolic glue solution followed by pyrolysis. This decreases the material's porosity and can be used as a way to modify its mechanical and thermal characteristics. Both the carbon matrices (resulted from the pyrolysis step) and the resultant SiC ceramics are shown to be pseudomorphous to the structure of initial cork. Depending on the synthesis temperature, 3 C -SiC, 6 H -SiC, or a mixture of these polytypes, could be obtained. By varying the mass ratio of initial carbon and silicon components, stoichiometric SiC or SiC:С:Si, SiC:С, and SiC:Si ceramics could be produced. The structure, as well as chemical and phase composition of the prepared materials were studied by means of Raman spectroscopy and scanning electron microscopy. Highlights: The method for the fabrication of complex-shaped porous ceramic hardware consisting of separate parts prepared from natural cork was proposed. By varying the synthesis temperature, 3 C -SiC or 6 H -SiC porous ceramic can be obtained.